2018
DOI: 10.1002/fsn3.766
|View full text |Cite
|
Sign up to set email alerts
|

Liver and plasma lipid changes induced by cyclic fatty acid monomers from heated vegetable oil in the rat

Abstract: Cyclic fatty acid monomers (CFAM) generated through domestic or industrial heating of vegetable oils may alter liver enzymes and induce hepatomegaly and steatosis, but the underlying mechanisms are not clearly understood. This study aimed to assess the effects of CFAM on liver and plasma lipids and to determine whether these effects are modulated by dietary lipids. Thirty‐six (36) male Wistar rats were fed either of the four isoenergetic diets consisting of canola oil or soybean oil with/without 500 mg/100 g C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The decrease in serum transaminases in groups fed with oils enriched with plant extracts could be explained by the low rancidity of these oil samples as previously observed with quality indices. Elevated transaminase levels in rats after consumption of fried oils had already been observed in a number of studies (Shastry et al, 2011;Badr El Said et al, 2015;Mboma et al, 2018). These results are also in agreement with Abdulaziz, Fasih, Saada, Khalid & Zarina, (2006), they showed that dietary supplementation with Nigella sativa limits the toxic effect of oxidised corn oil in rats by decreasing serum ALAT/ASAT concentrations.…”
Section: Effect Of the Different Oil Samples On Liver And Kidney Para...supporting
confidence: 77%
“…The decrease in serum transaminases in groups fed with oils enriched with plant extracts could be explained by the low rancidity of these oil samples as previously observed with quality indices. Elevated transaminase levels in rats after consumption of fried oils had already been observed in a number of studies (Shastry et al, 2011;Badr El Said et al, 2015;Mboma et al, 2018). These results are also in agreement with Abdulaziz, Fasih, Saada, Khalid & Zarina, (2006), they showed that dietary supplementation with Nigella sativa limits the toxic effect of oxidised corn oil in rats by decreasing serum ALAT/ASAT concentrations.…”
Section: Effect Of the Different Oil Samples On Liver And Kidney Para...supporting
confidence: 77%
“…The present study examined changes in hepatic triglyceride and cholesterol levels. Following the administration of heated oil, liver triglyceride levels increased, especially in 120‐TOSO and 240‐TOSO groups probably due to the formation of cyclic fatty acid monomers (CFAM) after thermoxidation of sunflower oil (Mboma et al, 2018). Previous studies indicated that cyclic fatty acid monomers (CFAM) were key factors in inhibiting metabolic enzymes, particularly liver lipase (Mboma et al, 2018; Narayanankutty et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Following the administration of heated oil, liver triglyceride levels increased, especially in 120‐TOSO and 240‐TOSO groups probably due to the formation of cyclic fatty acid monomers (CFAM) after thermoxidation of sunflower oil (Mboma et al, 2018). Previous studies indicated that cyclic fatty acid monomers (CFAM) were key factors in inhibiting metabolic enzymes, particularly liver lipase (Mboma et al, 2018; Narayanankutty et al, 2017). Following the thermoxidation of sunflower oil, CFMA formation and its inhibitory effects on hepatic lipase enzyme activity can increase serum/liver triglyceride levels (Narayanankutty et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, a recent animal study (Mboma et al, 2018a(Mboma et al, , 2018b has shown that CFAM from alpha-linolenic acid at 0.05% in no trans-fat diets has affected pro-atherogenic markers in a similar manner to trans fatty acids fed at much higher levels. Individual CFAM isomers in the canola and soybean oils used by Mboma et al ranged from 0.001% to 0.076% of the oil (Table 1), and the content was 10 times lower in the diets.…”
Section: Sirmentioning
confidence: 99%